2021
DOI: 10.1088/1742-6596/2094/5/052018
|View full text |Cite
|
Sign up to set email alerts
|

Counter-rotating electric generator for wind power plants with liquid metal energy transfer

Abstract: The problem of creating effective structures that ensure mutual rotation of the rotor and stator of an electric generator. The wide practical application of counter-rotor wind-electric generators, which provide a significant increase in specific power, is hindered by the disadvantages and low reliability of existing systems for removing electric energy from the windings of a rotating counter-rotor, due to the dry friction mode. It is possible to increase the reliability of the contact removal of electrical ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Since the proposed structure has two rotors, it exhibits twice the power density compared to the single-rotor structure [28,29]. In addition, the use of PM in the proposed structure leads to an increase in the reliability of counter-rotating wind turbine systems [3,31]. This structure is a good candidate to use in high-toque and low-speed applications such as gearless elevators [15].…”
Section: Introductionmentioning
confidence: 99%
“…Since the proposed structure has two rotors, it exhibits twice the power density compared to the single-rotor structure [28,29]. In addition, the use of PM in the proposed structure leads to an increase in the reliability of counter-rotating wind turbine systems [3,31]. This structure is a good candidate to use in high-toque and low-speed applications such as gearless elevators [15].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the electric generators for WECS, Booker et al (2010) andHabash et al (2011) proposed the use of counter-rotating electrical generators for wind turbine applications in urban areas, which have a mobile rotor (GR) and mobile stator (GS) rotating in opposite directions due to their increased energy performance compared to the conventional (with a fixed stator GS) generators. The counter-rotating generator was further investigated in terms of performance and rotor topology by Kutt et al (2020), Egorov et al (2021), andMirnikjoo et al (2021) and in terms of optimized system configuration with counter-rotating rotors (Mirnikjoo et al, 2020;Ullah et al, 2022a;Ullah et al, 2022b). Cho et al (2017) analyzedthe performance and control of a WECS with counterrotating rotors and counter-rotating generator and concluded that this configuration can lower the tip speed ratio at which the power curve attains its maximum almost by half in comparison to the single-rotor system.…”
mentioning
confidence: 99%